Employee Involvement in Corporate Social Responsibility and Employee Benefits - Andersen Demmangetung; Johnson Dongoran (Jurnal Manajemen Bisnis, 2023)
This study aims to analyze the extent of employee involvement in the implementation of Corporate Social Responsibility (CSR) and its benefits for employees and the company. The research method used is qualitative with a descriptive approach. The research sample used was as many as 5 people with data collection methods were interviews, observation and documentation. The results showed that employees of Yayasan Hasnur Centre Banjarmasin have different duties and responsibilities in implementing CSR, ranging from the process of designing programs that must be tailored to the needs of the community in certain areas, the process of socializing programs to the community to ensuring that programs really have an impact felt by the community. The role of these employees provides enormous benefits for each employee himself. The benefits felt by employees with their involvement in CSR programs are the provision of assistance according to employee needs, for example the provision of educational scholarships. Community recognition of assistance obtained from CSR activities in the region allows the company to continue to run its business activities without social pressure from refusal to do business in the region